The Dialogical Traveler: A Reading of Semprun's Le grand voyage - Sally M. Silk (Studies in 20th & 21st Century Literature, 1990)
In light of discourse theory influenced by Bakhtin's concept of dialogism, the notion of voice has changed significantly so that we are invited to read discourse in a way that represents a departure from Bakhtin. The theories of François Flahault, Michel Pêchetut, and John Frow, who inquire into the importance of conditions of production of language, are used to explore the vain search for a subject-centered voice in Jorge Semprun's Le Grand voyage. The narrating subject Gerard experiences "homelessness" in discourse because he fails to find a voice of his own. His relationship to music and literature depends on an other; in invasion of self by the other occurs so that Gerard speaks only through alien voices that confront him throughout the narrative. In discourse a decentering occurs that is not present at the thematic level: the protagonist arrives at a destination, but discourse does not.
Keywords: Bakhtin; discourse theory; dialogism; voice; discourse; François Flahault; Michel Pêchetut; John Frow; subject-centered voice; subject-centered; Jorge Semprun; Le Grand voyage; narrating subject; Gerard; homelessness; music; literature; relationship; invasion of self; self; alien; speak; speaks; narrative; decentering; protagonist; destination